KUALITAS PELAYANAN PUSKESMAS 01 WELERI KECAMATAN WELERI KABUPATEN KENDAL - Bayu Putra Pratama; Susi Sulandari; Margareta Suryaningsih (Journal of Public Policy and Management Review, 2016)
Public service is the responsibility of the government and implemented by government agencies, be it in the central, local, and the environment of the State Owned Enterprises. One form of public service implemented by the government is fulfilling the needs of public health. Public Health Centre is one of the public organizations that provide health services to the people in the sub-district area. The existence of Public Health Centre because it is became the spearhead of the health services provided by local governments. This study aimed to describe the quality of services provided by 01 Public Health Centre Weleri to know what are the dimensions that hamper and support the service quality in 01 Weleri Public Health Centre. The type of research used is qualitative descriptive which look at the quality of service through the five dimensions of service that is tangible, reliability, responsiveness, assurance, and empathy. The results showed that the dimensions that support the services at the 01 Public Health Centre Weleri are responsiveness and assurance while the dimensions that hamper are tangible, reliability, and empathy. This is proved by the results of interviews and field observations of researcher who showed that patients of 01 Public Health Centre 2 Weleri satisfied with the responsiveness and assurance given but patients are assessing tangible, reliability, and empathy given are still not good.